Monitoring Drug Adherence - Lieber, Sarah R (Transplant Rev (Orlando), 2015)
TOPIC: Medication nonadherence is prevalent in transplant recipients and is a major reason for graft loss. The present review discusses the measurement of adherence in transplant recipients and strategies to improve adherence. SOURCES REVIEWED: since adherence research is not confined to transplant recipients, our literature review included studies relevant to transplant recipients as well as adherence to medical recomemndations more generally. We reviewed manuscripts in the English language indexed in PubMed Central, as well as ancillary sources of information such as textbook chapters that are not indexed. CONCLUSION: There is no consensus in the literature about an optimal way to monitor adherence, nor is there agreement about a preferred management strategy. Until definitive studies demonstrate the effectiveness of intervention strategies, knowledge of the monitoring as well as intervention methods that are described in this review is expected to give practitioners the initial tools to deal with nonadherence as an important aspect of patient care.